From political opposition in speech: The polemic reformulation in Colombian guerrilla rhetoric - Olave Arias, Giohanny (2016)
This article analyzes the use of rhetorical polemic reformulation process in the speech of the guerrillas of the Revolutionary Armed Forces of Colombia. A corpus with articles published in the online journal, Resistencia, 2010-2012 editions, consulted the websites of the insurgent group, and emergent categories were extracted by inductive analysis. As a result, reformulation types that appear in the sample and their co-occurrence with polyphonic denials described reinforcing function. The findings point to interpret the reformulation as a way to oppose the central government, through the controversial and argumentative mode. In this case, reformulation is key in the effort to build forms of political divergence in discourse, because it reinforces the distance between the actors and involves the problem of truth in the speeches of the internal armed conflict.